2019
DOI: 10.17269/s41997-019-00208-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of flavouring chemicals and potential toxicants in e-cigarette products in Ontario, Canada

Abstract: Objectives The current study examined constituents of e-cigarette products on the Canadian market, with a focus on the province of Ontario. Methods E-cigarettes were systematically purchased at 80 retail outlets across 4 cities in Ontario, Canada, in January-February 2015. Product constituents were identified using gas chromatography and mass spectrometry. Additionally, tobacco-specific nitrosamines (TSNAs) were quantified in tested products using liquid chromatography with tandem mass spectrometry. Results A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 25 publications
2
30
0
2
Order By: Relevance
“…For example, P. Callahan-Lyon (2014) reported that the main components of e-liquids, such as glycol and glycerol, when vaporized, can cause throat, mucous membranes, and eye irritation [50]. In addition, found similar results when analyzing health associated risks of e-cigarettes in Canadian populations [51].…”
Section: Supplementary Materialsmentioning
confidence: 93%
“…For example, P. Callahan-Lyon (2014) reported that the main components of e-liquids, such as glycol and glycerol, when vaporized, can cause throat, mucous membranes, and eye irritation [50]. In addition, found similar results when analyzing health associated risks of e-cigarettes in Canadian populations [51].…”
Section: Supplementary Materialsmentioning
confidence: 93%
“…25 Measurable levels of tobacco-specific nitrosamines were detected in 70% of tested products. 25 Further studies suggest that use of e-cigarettes may negatively influence cardiovascular health 27 and that flavorants in e-cigarettes present potential hazards, such as risk of obstructive lung diseases. 28 In addition, nicotine, often used in vaping, confers a series of risks, including anomalies in the development of the hippocampus and cerebral cortex among adolescents.…”
Section: Potential Health Risksmentioning
confidence: 98%
“…Studies on e-cigarette products, including disposable and refillable commercial articles, and e-liquids, report that they contain an average of 6.2 flavoring chemicals, and that e-cigarettes with sweet flavors have a significantly greater number of flavoring chemicals when compared with tobacco-and menthol-flavored products. 25 More than 20% of commercial products were found to contain flavoring chemicals with a potential risk of inhalation toxicity, including benzyl alcohol, benzaldehyde, and vanillin. 25,26 Additional toxicants, such as acrolein and diacetyl, have been identified in several vaping products.…”
Section: Potential Health Risksmentioning
confidence: 99%
See 2 more Smart Citations